The central chemosensitivity is not altered by cerebral erythropoietin. (16th November 2015) - Ballot, Orlane; Laouafa, Sofien; Elliot-Portal, Elizabeth; Tam, Rose; Voituron, Nicolas; Joseph, Vincent; Soliz, Jorge
Highlights: Cerebral erythropoietin is a potent respiratory stimulant under conditions of normoxia and hypoxia. Cerebral erythropoietin does not contribute to the modulation of the central regulation induced by hypercapnic stimulus. Abstract: The stimulation of central chemoreceptors by CO2 is considered essential for breathing. The supporting evidence include the fact that central apnea in neonates correlates with immaturity of the CO2 -sensing mechanism, and that congenital central hypoventilation syndrome (CCHS) is characterized by the absence of a ventilatory response to elevated PCO2 . We reported previously that cerebral erythropoietin (Epo) is a potent respiratory stimulant upon normoxia and hypoxia. The injection of soluble Epo receptor (sEpoR; the natural EpoR competitor to bind Epo) via the cisterna magna (ICI: intra-cisternal injection) decreases basal ventilation in adult and newborn mice. Moreover, sEpoR induces respiratory depression in adult and newborn mice exposed to hypoxia. In this study we tested the hypothesis that endogenous brain Epo also modulates the respiratory stimulation induced by the activation of central CO2 chemoreceptors. Adult and newborn male and female mice received an injection of sEpoR or vehicle via the cisterna magna. Twenty-four hours later basal minute ventilation and the ventilatory response to hypercapnia (5% CO2 ) were evaluated by plethysmography. Our results did not show a difference in the hypercapnic response between sEpoR and vehicle-injected male or female mice at postnatal or adult ages. We concluded that endogenous brain Epo does not contribute to modulating the PCO2 -mediated central activation of breathing.